(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2023)
This article describes the genetic analysis of vegetable bean hybrids. Hybridization makes it possible to combine a number of forms of resistance to individual pests or to different types of pests and diseases in a single variety. In the course of selection, plants of the second generation are selected from the hybrid population, characterized by a greater degree of their resistance to pests and other economically valuable traits. The highest percentage of cross-pollination was achieved due to a longer period of simultaneous flowering in the parent pairs. The set of vegetable beans during artificial hybridization directly depends on the time of pollination, as well as on the year of sowing and weather conditions.